Trends of Serum Electrolyte Changes in Crush syndrome patients of Bam Earthquake; a Cross sectional Study - Saeed Safari; Mehdi Eshaghzade; Iraj Najafi; Alireza Baratloo; Behrooz Hashemi; Mohammad Mehdi Forouzanfar; Farhad Rahmati (Emergency, 2016)
Introduction: Electrolyte imbalances are very common among crushed earthquake victims but there is not enough data regarding their trend of changes. The present study was designed to evaluate the trend of changes in sodium, calcium, and phosphorus ions among crush syndrome patients. Methods: In this retrospective cross-sectional study, using the database of Bam earthquake victims, which was developed by Iranian Society of Nephrology following Bam earthquake, Iran, 2003, the 10-day trend of sodium, calcium, and phosphorus ions changes in > 15 years old crush syndrome patients was evaluated. Results: 118 patients with the mean age of 25.6 § 6.9 yearswere studied (57.3 male). On the first day of admission, 52.5% (95% CI: 42.7 - 62.3) of the patients had hyponatremia, which reached 43.9% (95% CI: 28.5 - 59.3) on day 10. 100.0% of patients were hypocalcemic on admission and serum calcium level did not change dramatically during the 10 days of hospitalization. The prevalence of hyperphosphatemia on the first day was 90.5% (95% CI: 81.5 - 99.5) and on the 10th day of hospitalization 66.7% (95% CI: 48.5 - 84.8) of the patients were still affected. Conclusion: The results of the present study shows the 52.5%prevalence of hyponatremia, 100% hypocalcemia, and 90.5% hyperphosphatemia among crush syndrome patients of Bam earthquake victims on the first day of admission. Evaluation of 10-day trend shows a slow decreasing pattern of these imbalances as after 10 days, 43.9% still remain hyponatremic, 92.3% hypocalcemic, and 66.7% hypophosphatemic.